Energy-effectively printed all-polymer solar cells exceeding 8.61% efficiency. (April 2018) - Lin, Yuanbao; Dong, Sheng; Li, Zhaojun; Zheng, Wenhao; Yang, Junyu; Liu, Alei; Cai, Wanzhu; Liu, Feng; Jiang, Yufeng; Russell, Thomas P.; Huang, Fei; Wang, Ergang; et al.
Abstract: All-polymer solar cells (all-PSCs) have attracted tremendous attention in the past few years due to their unique advantages. However, up to now most of high-efficiency all-PSCs are processed by spin-coating with complicated post treatment processes, which is ill-suited to a large-area roll-to-roll (R2R) technique. In this work, high-efficiency all-PSCs based on PTB7-Th and PNDI-T10 are achieved by one of R2R compatible printing techniques, i.e. doctor-blading, without any annealing treatment. It was found that incorporating an additive into all polymer blends solution can prolong the drying time of all polymer nanocomposites from 120 to 1000 s to form a better bulk heterojunction morphology and a higher crystallinity, which thus reduce charge recombination and show much better electrical impedance spectroscopy parameters. Record-breaking power conversion efficiencies (PCEs) of 8.61% and high fill factors (FF) of 0.71 are achieved by doctor-blading under an extremely process-simple and energy-effective conditions. Moreover, large-area (2.03 cm 2 ) flexible ITO-free all-PSCs by doctor-blading with record-breaking PCEs of 6.65% and FF of 0.65 are realized, which are much higher than conventional fullerene-based ones under the same condition, demonstrating that all-PSCs are more suitable for the flexible device structure and have a bright future towards practical application with R2R manufacture. Graphical abstract: Higher-efficiency all polymer solar cells are fabricated by an industrially suitable doctor-blading technique in ambient atmosphere than that by spin-coating in nitrogen atmosphere. The favourable phase separation with optimized crystallization and interpenetrating polymer networks can be achieved by incorporating 1, 8-diiodooctane into chlorobenzene, owing to the prolonged drying time of the all-polymer active film from 120 to 1000 s. Consequently, the highest PCEs of 8.61% and 7.12% are obtained in printed all-PSCs with ITO-based rigid substrate and ITO-free flexible substrate to date, respectively.fx1 Highlights: The highest PCE of 8.61% in all polymer solar cells (all-PSCs) is achieved by an energy-effective doctor-blading technique. A high FF of 0.71 is obtained by incorporating an additive for optimizing nanoscale morphology and crystallinity. Large-area all-PSCs are successfully manufactured with a PCE of 6.65%, which is highest in flexible ITO-free all-PSCs. There is only 6.6% efficiency drop in flexible ITO-free printed all-PSCs increasing the device area from 0.14 to 2.03 cm 2 .